Perkembangan Bentuk Nisan Aceh, Sebagai Wujud Kreativitas Masyarakat Aceh Pada Masa Lalu - Repelita Wahyu Oetomo (Balai Arkeologi Sumatera Utara, 2009)
AbstractAt least, there are 3 (three) periods of Islam art development in Aceh. First, the beginning of the expansion of Islam. In that era, the element of Islam’s art assimilated to the art of preislam (Hindu-Buddha). In line with the development of Aceh government system, people began to increase the skill in art. But, when the Dutch nation colonized, the art in Aceh was fading. It was known through the gravestones.